Proposal and design of a new biomass based syngas production system integrated with combined heat and power generation. (15th August 2017) - Prakash, M.; Sarkar, A.; Sarkar, J.; Mondal, S.S.; Chakraborty, J.P.
Abstract: A novel process model has been proposed for biomass gasification integrated with combined heat and power generation using various biomass, which have been selected based on availability in abundant quantities from different regions of India. In the proposed system, high thermal energy carried out by gasification products has been utilized to operate a combined heat and power cycle system consisting of steam and organic Rankine cycles with provisions of air and water heating. Syngas, a mixture of hydrogen and carbon monoxide, has been obtained as the final product which has potential for many applications. The influences of various operating parameters such as water to biomass ratio, mass flow rate, reactor temperature and type of biomass on the methane, syngas, total combustible gas and hydrogen productions and performance index have been studied. Gasification temperature has been optimized for maximum syngas production. Study shows that the best performance in term of CHP does not simultaneously ensure maximum syngas production. Hence, a trade off is required between CHP and syngas production for biomass selection. Highlights: Novel system layout is proposed for biomass gasification integrated with CHP. Production syngas and CHP using steam and organic Rankine cycles from various biomasses. Gasification temperature has been optimized for maximum syngas production. Influences of WBR and type of biomass on the syngas and performance are studied. Trade off is required between CHP and syngas production for biomass selection.